EFEKTIVITAS ETHYL METHANE SULFONATE (EMS) TERHADAP PEMBENTUKAN TANAMAN WORTEL (Daucus carota L.) MANDUL JANTAN - Gungun Wiguna; Rd. Prasodjo Prasodjo; Uun Sumpena (MEDIAGRO, 2011)
The study was conducted at Indonesian Vegetable Research Institute in March to December  2009 with an  altitude of  1250 masl.  The  objective of study was  to determine the  effectiveness of  EMS  in  producing  carrots male  sterile.  The experiment was arranged in Complitely  Randomized  Block  Design  with  two factors  and three replication.  The results indicate  that the  local  carrot  cultivars have the survival to maturity better than hybrid varieties. The highest percentage of  living  plants  showed  by  carrot  cultivar  origin  Cipanas  (73.21%).  The percentage of live plants is affected by the EMS treatment only until the age of 60 HST.  Increased concentrations of EMS  resulted in  decreased  percentage of  live plants.  Increased concentrations of  EMS  also  tends to  reduce the weight of thousand grains carrot seed produced from the M1 generation. Visual appearance of  pollen  on  all  EMS  treated  the same as the  control, that is  pithy  and  bright yellow. Treatment of  various EMS  concentrations level  provided  the individual has not been effective in producing carrots male sterile. Key words: carrot, male sterile, EMS.